2008
DOI: 10.1080/08838150801991773
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Change on TV: How Viewer-Controlled Changes in Content Differ From Programmed Changes in Content

Abstract: Two experiments explored differences in television viewers' responses to viewercontrolled and producer-controlled content changes. Viewers in both studies could change channels among 4 different newscasts. Orienting, sympathetic activation, cognitive effort, and recognition were compared in the moments following both channel changes (viewer control) and cuts (producer control). Neither channel changes nor cuts elicited orienting. Sympathetic activation was higher following channel changes, while cognitive effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Wang et al have suggested that increased boredom leads to channel changes (Wang et al, 2006), and have found that arousing media content causes large increases in SCL and is a significant predictor when modeling dynamic channel-changing behavior (Wang et al, 2011). Other studies (Lang et al, 2005;Wise, Lee, Lang, Fox, & Grabe, 2008) found that switches during television viewing are usually associated with a particular trend in sympathetic arousal: linear decreases up until the moment of a switch and brief periods (seconds) of heightened arousal after a switch. As the authors note, this suggests that viewing is a relatively passive, low-involvement experience.…”
Section: Media Multitasking: Concurrent Devices Versus Serial Switchingmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al have suggested that increased boredom leads to channel changes (Wang et al, 2006), and have found that arousing media content causes large increases in SCL and is a significant predictor when modeling dynamic channel-changing behavior (Wang et al, 2011). Other studies (Lang et al, 2005;Wise, Lee, Lang, Fox, & Grabe, 2008) found that switches during television viewing are usually associated with a particular trend in sympathetic arousal: linear decreases up until the moment of a switch and brief periods (seconds) of heightened arousal after a switch. As the authors note, this suggests that viewing is a relatively passive, low-involvement experience.…”
Section: Media Multitasking: Concurrent Devices Versus Serial Switchingmentioning
confidence: 99%
“…Some studies have examined how processing differs between user‐ and device‐driven switches, finding that increases in physiological arousal after a channel change (Wise et al, ) or new picture onset on a computer screen (Wise & Reeves, ) are relatively greater when switches are initiated by users. That is, across different media devices, user control over task switches is associated with heightened arousal.…”
Section: Media Multitasking: Concurrent Devices Versus Serial Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, central details are prioritized or privileged in terms of encoding. Research on automatic and controlled information processing provides compelling evidence that people notice and pay attention to details not only because people are consciously looking for them, but also because they are readily available to people due to their size, proximity, dynamism, and other physical properties (Wise, Lee, Lang, Fox, & Grabe, 2008). Advertising research has reliably replicated the preferential processing effect for object size (e.g., Burtt, 1938;Grabe & Bucy, 2009), object number (Reynolds & Miller, 2009), brightness and contrast (see also Palmer, 2003), location on page/screen (Lucas & Britt, 1950), and proximity to the viewer and camera angle (Grabe & Bucy, 2009), as well as dynamic factors such as objects in motion/action (Shipley & Zacks, 2008), camera zoom-in and zoom-out and over-the-shoulder camera technique (Grabe, Zhou, & Barnett, 2001), and camera changes Downloaded by [University of Saskatchewan Library] at 23:02 13 March 2015 .…”
Section: Studymentioning
confidence: 99%
“…However, Lecheler et al (2015) argue that the specific content of a message, regardless of its positive or negative connotation, is what elicits high emotional responses, which can in turn, dictate retention. Wise et al (2008) consider both producer and viewer cuts and channel changes during a news program to have a significant effect on cognitive processing. Moments leading up to a change in stimulus, as controlled by the viewer, were found to produce less cognitive processing, while effort, arousal and encoding were increased when presented with the new stimulus (Lang et al, 2005).…”
Section: News Crawls Recall and Retentionmentioning
confidence: 99%